A CONTENT ANALYSIS OF THE ISLAMIC EDUCATION TEXTBOOK IN MALAYSIA - Ismail, Halim; Raslan, Nurul Afiqah; Hussien, Suhailah; Saiful Azizi Nik Abdullah, Nik Md.; Sahrir, Muhammad Sabri; Ismai, Noor Azizi (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2023)
Islamic Education is often taught as an academic subject like any other subject. The discipline of teaching Islamic doctrine and beliefs (Aqidah) requires a change of paradigm in both methodology and content. This is important to educate Muslim students to respond critically to modern challenges. The present study aims to analyze the Islamic Education Textbook of Secondary School (KSSM) in Malaysia on inculcating Aqidah (faith) for Form 1 students. One of the topics from the textbook was chosen for analysis, i.e., 'Islam, Religion of Fitrah.’ The research used a qualitative content analysis method on the Islamic Education Form 1 Textbook from the Ministry of Education. Findings suggested that the Islamic Education Textbook should focus on developing the best and most informative content while encouraging students to act and reflect on their role as vicegerent of Allah through its structure, content, layout, and design. Finally, the study offers suggestions on how the textbook can be improved to facilitate effective teaching of Aqidah to the students.